Sympathetic and hemodynamic responses to exercise in heart failure with preserved ejection fraction - Manabe, Kazumasa; D’Souza, Andrew W.; Washio, Takuro; Takeda, Ryosuke; Hissen, Sarah L.; Akins, John D.; Fu, Qi (Frontiers in Cardiovascular Medicine, 2023)
Excessive sympathetic activity during exercise causes heightened peripheral vasoconstriction, which can reduce oxygen delivery to active muscles, resulting in exercise intolerance. Although both patients suffering from heart failure with preserved and reduced ejection fraction (HFpEF and HFrEF, respectively) exhibit reduced exercise capacity, accumulating evidence suggests that the underlying pathophysiology may be different between these two conditions. Unlike HFrEF, which is characterized by cardiac dysfunction with lower peak oxygen uptake, exercise intolerance in HFpEF appears to be predominantly attributed to peripheral limitations involving inadequate vasoconstriction rather than cardiac limitations. However, the relationship between systemic hemodynamics and the sympathetic neural response during exercise in HFpEF is less clear. This mini review summarizes the current knowledge on the sympathetic (i.e., muscle sympathetic nerve activity, plasma norepinephrine concentration) and hemodynamic (i.e., blood pressure, limb blood flow) responses to dynamic and static exercise in HFpEF compared to HFrEF, as well as non-HF controls. We also discuss the potential of a relationship between sympathetic over-activation and vasoconstriction leading to exercise intolerance in HFpEF. The limited body of literature indicates that higher peripheral vascular resistance, perhaps secondary to excessive sympathetically mediated vasoconstrictor discharge compared to non-HF and HFrEF, drives exercise in HFpEF. Excessive vasoconstriction also may primarily account for over elevations in blood pressure and concomitant limitations in skeletal muscle blood flow during dynamic exercise, resulting in exercise intolerance. Conversely, during static exercise, HFpEF exhibit relatively normal sympathetic neural reactivity compared to non-HF, suggesting that other mechanisms beyond sympathetic vasoconstriction dictate exercise intolerance in HFpEF.